Correlation Between Transabdominal Sonographically Measured Prostate Volume with Anthropometric Factor in Normal Healthy Subjects - Monowara, Mahmuda; Ahmed, Akhter Uddin; Mohiuddin, Abu Saleh; Taher, Mohammad Abu; Nasrin, Zinat; Hossain, Mohammad Mahbub (BIRDEM Medical Journal, 2012)
To investigate the relationship between total prostate volume with anthropometric factor like age, height, weight and BMI. This can be useful in assessing the normality of prostate gland. Method: In 42 normal healthy subjects the length, anteroposterior and transverse diameters of prostate gland were measured & prostate volumes were calculated by using prolate ellipse formula. Age, height, weight of the subjects were recorded and body mass index calculated accordingly. Result: Correlation co-efficient or r test was used to find out the relationship between the variables. P value <0.05 was considered as statistically significant. Total prostatic volume correlation coefficient with age, weight and BMI were 0.907, 0.883 and 0.352 (p<0.001) respectively, but no significant correlation (r=0.133; p>0.05) was found between prostatic volume and height. Conclusion: Total prostate volume has a strong significant linear relationship & age, weight & BMI. But height does not correlate significantly with total prostate volume. Thus anthropometric factors like age, weight, BMI can therefore be used to predict prostate volume prior to ultrasound. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12359 Birdem Med J 2012; 2(1) 29-32